Manual on Evaluation Advisory Committees/Boards of Programme Evaluation Organisation/States/UTs - Planning Commission (Planning Commission, 1997)
The book provides a comprehensive overview of the composition and functions of various Evaluation Advisory Committees and Boards across different states in India. It outlines the roles of key members, including Chief Secretaries, Finance Secretaries, and Directors of Evaluation, in the evaluation process of government schemes and programs. The committees are tasked with selecting evaluation studies, approving reports, and ensuring the implementation of recommendations. The structure and responsibilities of these committees aim to enhance the effectiveness of public programs through systematic evaluation and follow-up actions.
Programme Evaluation Organisation Planning Commission, Govt. of India New Delhi March, 1997
Programme Evaluation Organisation Planning Commission
Keywords: Evaluation Advisory Committee; Chief Secretary; Finance Secretary; Evaluation Unit; Draft Evaluation Report; Implementation Recommendations; Statistical Activities; Evaluation Studies; Planning Department; Economic & Statistical Adviser